2019
DOI: 10.1002/jrs.5539
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries of modes in Ni3V2O8: Polarized Raman spectroscopy and ab initio phonon calculations

Abstract: Knowledge of symmetries of vibrational modes is essential for understanding the mechanism of structural transitions and spin‐phonon coupling in multiferroics where phonons play a vital role. Using polarized Raman spectroscopy, we have identified and assigned symmetries of 30 out of the 36 expected Raman active modes in Ni3V2O8. The zone‐centred phonon mode wavenumbers are calculated using ab initio calculations. The gerade mode wavenumbers are compared with our polarized Raman data whereas ungerade mode wavenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The remaining modes between 500 and 900 cm −1 correspond to V-O stretching; however, as O atoms are also connected to Mg atoms, these modes are mixed with some bending and stretching of Mg-O. 39,40 Next, the power-dependent Raman spectroscopy is carried to further investigate the photostrictive origin, for which one mode is analyzed from all the three aforementioned frequency regions. It is observed that with increasing laser power, all the three phonon modes identified with excitation wavelength 473 nm (Figure 6B), 532 nm (Figure 6C), and 632 nm (Figure 6D) undergo different degrees of redshift, indicating the light-induced distortion of MgO 6 and VO 4 polyhedrals owing to change in the interatomic distances, which consequently results in the overall expansion of the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining modes between 500 and 900 cm −1 correspond to V-O stretching; however, as O atoms are also connected to Mg atoms, these modes are mixed with some bending and stretching of Mg-O. 39,40 Next, the power-dependent Raman spectroscopy is carried to further investigate the photostrictive origin, for which one mode is analyzed from all the three aforementioned frequency regions. It is observed that with increasing laser power, all the three phonon modes identified with excitation wavelength 473 nm (Figure 6B), 532 nm (Figure 6C), and 632 nm (Figure 6D) undergo different degrees of redshift, indicating the light-induced distortion of MgO 6 and VO 4 polyhedrals owing to change in the interatomic distances, which consequently results in the overall expansion of the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%
“…among the total of its 36 (10A g + 8B 1g + 7B 2g + 11B 3g ) modes might be due to their weak intensity or overlapping with other modes due to accidental degeneracy. 40 However, in the comparative analysis between the Raman spectra observed with excitation wavelength 532 and 632 nm, the intensity of the Raman spectra while satisfying I ∝ (excitation wavelength) −4 should be higher under excitation wavelength 532 nm than that with excitation wavelength 632 nm 41 ; but for Mg 3 V 2 O 8 ceramic, we observed that the intensity of the phonon modes with excitation wavelength 632 nm is comparable and even higher than the intensity of modes identified with excitation wavelength 532 nm (Figure S6), which indicates the resonating interactions for Mg 3 V 2 O 8 when irradiated with laser 632 nm. Pertinent to mention, all the modes have some contributions from vibrations of the main constituents as described in Figure 6A, but at resonant interaction their effect becomes more pronounced, which could be the possible origin of higher value for η observed in Figure 4C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DFT-calculated ω 0 has a related uncertainty of ±5%. Discrepancies in symmetry assignation with Kesari et al 53 Using crossed polarization, the B 1g modes were identified when inciding along the z-axis (6 out of 8), B 2g modes, with yincidence (6 out of 7), and a mixture of B 1g and B 3g , in the ξaxis (7 out of the 11 total B 3g ). There was no polarization leakage in any of the spectra, except for the most intense mode, A g 10 , which was also measured in crossed polarization at orientations z and ξ.…”
Section: Ambient Conditions For Polarized Raman (Ni 3 V 2 O 8 and Co ...mentioning
confidence: 87%
“…Jauhari et al [148] described their study of structural phase transitions in barium titanate modified sodium niobate using Raman scattering and found their results consistent with prior X-ray diffraction. Kesari et al [149] reported the symmetries of modes in Ni 3 V 2 O 8 using polarized Raman spectroscopy and ab initio phonon calculations. Nguyen et al [150] reported Raman spectroscopic evidence of impurity-induced structural distortion in SmB 6 .…”
Section: Single Crystalsmentioning
confidence: 99%